Penerapan PJBL Berbantu METASIA (Media Peta Indonesia) untuk Meningkatkan Literasi Siswa pada Materi IPAS Kelas 5 SD Bukit Aksara - Ningsih, Heti Puspita; Nuvitalia, Duwi; Purnamasari, Veryliana; Warsiti, Bernadeta (LPPM Universitas PGRI Argopuro Jember, 2024)
This research aims to apply the Project Based Learning model assisted by METASIA (Media Peta Indonesia) to increase student literacy in grade 5 science and science material at Bukit Aksara Elementary School. It is also hoped that this research will be able to open the horizon of knowledge about the importance of learning innovation in facing developments in the times that are increasingly changing. Therefore, this research will describe the implementation of PjBL assisted by METASIA (Media Peta Indonesia) to increase students' literacy in grade 5 science material at Bukit Aksara Elementary School. This research uses a qualitative research approach, while the type of research method used is qualitative. Researchers analyzed the implementation of PJBL assisted by METASIA (Media Peta Indonesia) to increase students' literacy in grade 5 science material at Bukit Aksara Elementary School. The subjects of this research were class V students at Bukit Aksara Elementary School. The instrument in this research used to help researchers collect data is using a literacy interest questionnaire sheet and documentation, namely data produced directly by the researcher through a literacy interest questionnaire for class V students at Bukit Aksara Elementary School when learning using the PjBL model with the help of METASIA (Media Peta Indonesia ).